Mechanisms of Cooperation between Pre-School Education and School - Rakhimberdiyevna, Ismailova Mubarak (International Journal on Integrated Education, 2023)
This article talks about the content, mechanisms, methods and tasks of cooperation between the preschool educational organization and the school.